Implementasi Pendidikan Agama Buddha Berwawasan Multikultural dalam Membangun Sumber Daya Manusia Berkualitas di Sekolah - Satya Raz, Purna (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
The aim of this study is to explore the implementation of multiculturaloriented Buddhist Religious Education in shaping high-quality human resources who are tolerant, wise, and able to live peacefully amidst diversity. This study adopts a qualitative descriptive approach, specifically descriptiveanalytic. This approach was chosen to obtain a comprehensive understanding of the Buddhist learning process that integrates multicultural values. The research was conducted at YPSIM using data collection techniques such as: (1) observation, (2) in-depth interviews, and (3) documentation The findings reveal that Buddhist Religious Education at YPSIM is implemented contextually and transformatively. Teachers integrate universal Buddhist values such as mettā (loving-kindness) and karuṇā (compassion) through participatory methods like case studies, interfaith discussions, and social simulations. Students exhibit increased inclusivity, empathy, and openness to differences. The physical and cultural environment of the school also supports the creation of a welcoming and multicultural learning atmosphere. These findings reinforce the concept of multicultural education, particularly in terms of content integration, prejudice reduction, equitable learning strategies, and strengthening school culture. Buddhist religious education has proven to be an effective instrument in shaping students' character, enabling them to live harmoniously amidst cultural and religious diversity. Keywords: Buddhist Religious Education, Character, Human Resources (HR), Multicultural, Tolerance.